Uniform in Time Description for Weak Solutions of the Hopf Equation with Nonconvex Nonlinearity - Antonio Olivas Martinez; Georgy A. Omel'yanov (International Journal of Mathematics and Mathematical Sciences)
We consider the Riemann problem for the Hopf equation with concave-convex flux functions. Applying the weak asymptotics method we construct a uniform in time description for the Cauchy data evolution and show that the use of this method implies automatically the appearance of the Oleinik E-condition.